Penimbunan Bahan Bakar Minyak (BBM) Tanpa Izin yang Disubsidi Pemerintah dalam Persperktif Pidana - Muhammad Aksah Sahudi; Herman Balla; Auliah Ambarwati (Jurnal Litigasi Amsir, 2023)
This study aims to determine the application of criminal sanctions against the perpetrators of the Hoarding of Fuel Oil (BBM) Without a Government Subsidized Permit based on the Case Study in Decision No. 266/Pid.Sus/2019/PN.Pli and To find out the judge's considerations in imposing a crime on the Crime of Stockpiling Oil Fuel (BBM) Without a Government Subsidized Permit based on the case study in Decision No. 266/Pid.Sus/2019/PN.Pli. This study uses a type of normative research with a statutory approach (statute approach) and approach (study) case (case approach). Sources of legal materials use primary legal materials and secondary legal materials. The results of the research show that the application of criminal sanctions against the perpetrators of the stockpiling of government-subsidized fuel oil (BBM) is based on the case study in decision No. 266/Pid.Sus/2019/PN.Pli the public prosecutor charged the defendant with alternative charges, namely Article 55, Article 53 letter b, and Article 53 letter c of Law Number 22 of 2001 concerning Oil and Gas, and the judge imposed criminal sanctions against the defendant based on the public prosecutor's third alternative indictment. The judge's considerations in imposing a sentence on the crime of hoarding fuel oil (BBM) without a permit subsidized by the government is based on the case study in decision no. 266/Pid.Sus/2019/PN.Pli namely by looking at aspects of juridical considerations including witness statements, evidence, and the defendant's statement resulting in legal facts that were revealed in court then the judge considered the elements contained in Article 53 letter c of the Law -Law Number 22 of 2001 concerning Oil and Natural Gas to impose a sentence on the defendant, and the judge considers aggravating and mitigating circumstances for the defendant.